2014
DOI: 10.1073/iti0114111
|View full text |Cite
|
Sign up to set email alerts
|

In This Issue

Abstract: In This Issue Emotional signs of approaching depressionComplex systems approaching a tipping point typically experience a period called "critical slowing down, " in which the system's resilience and recovery from perturbations slow prior to a change in state. To assess whether such critical slowdown precedes a shift between healthy and depressed emotional states, Ingrid van de analyzed studies in which volunteers recorded their emotions at random times over 5 or 6 days. The authors focused on reports provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 2 publications
2
18
0
Order By: Relevance
“…The product of a single gene, the IR precursor is processed in the trans-Golgi network to form a disulfide-linked (␣␤) 2 homodimer (14). The extracellular ␣ subunits bind insulin, and the transmembrane ␤ subunits contain the intracellular TK domains (15). Whereas the structure of the holoreceptor has been visualized only at low resolution (Ͼ20 Å (16)), its domain dissection has enabled stepwise crystallographic analysis.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The product of a single gene, the IR precursor is processed in the trans-Golgi network to form a disulfide-linked (␣␤) 2 homodimer (14). The extracellular ␣ subunits bind insulin, and the transmembrane ␤ subunits contain the intracellular TK domains (15). Whereas the structure of the holoreceptor has been visualized only at low resolution (Ͼ20 Å (16)), its domain dissection has enabled stepwise crystallographic analysis.…”
mentioning
confidence: 99%
“…(ii) The structure of the N-terminal three domains of the ␣ subunit (Leu-rich domain 1, Cysrich domain, and Leu-rich domain 2; L1-CR-L2) has been determined at 2.3 Å (19). (iii) The structure of the dimeric ectodomain ((␣␤ ⌬ ) 2 , containing the entire ␣ subunit and the extracellular portion of the ␤ subunit, ␤ ⌬ ) has been determined at 3.3 Å (20), wherein its conformation resembles an inverted V. Although co-crystals of an insulin-ectodomain complex have not been obtained, a variety of evidence indicates that insulin binds within the crux of the dimer (15,21,22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A flat DOPC/MO SLB can be observed except for a few defects in figure 2(H). As DOPC exhibits a lower phase transition temperature (−18 ± 1 °C) than DPPC [24, 25], DOPC vesicles are in the liquid crystal phase. It has been reported that liquid crystal phase phospholipid vesicles can form an SLB with few defects [2628].…”
Section: Resultsmentioning
confidence: 99%